Age-related language performance and device use in children with very early bilateral cochlear implantation - Glaubitz, Cynthia; Liebscher, Tim; Hoppe, Ulrich (International Journal of Pediatric Otorhinolaryngology, 2021)
Objectives: Paediatric cochlear implantation within the first year of life results in better outcome in auditory and language skills. Beside individual, audiological and social factors, quantity and quality of daily cochlear implant (CI) use also seem to be an influencing factor. The purpose of this study was to evaluate children's early receptive and expressive language performance considering bilingual language development as well as quantity and quality of daily CI use and intraoperative objective measurements. Methods: The retrospective analysis included data from 35 very early bilaterally cochlear-implanted children (age at CI M = 8.4 +/- 1.5 months). Language performance was assessed by the German standardised test SETK-2 (age at testing M = 29.4 +/- 4.0 months). The CI system-integrated data-logging was analysed with regard to daily CoilOn-time, CoilOff and exposure to classified listening scenes. Intraoperatively measured thresholds of evoked compound action potentials (T-ECAPs) were analysed to ensure CI functionality. Results: The cohort showed language performance within the normal range for word comprehension, sentence comprehension and word production, level of sentence production was reduced. Overall, bilingual children performed less well than monolingual children. Intraoperative T-ECAPs were recorded for the total cohort and no anomalies were detected. Children used their CI for about 8.7 +/- 1.4 h per day, most of this time spent in a quiet environment (38%). Word production was significantly correlated with the daily duration of CI use (CoilOn-time) and with exposure to the listening environment Speech. No correlation was found between number of daily coil disconnections (CoilOff) and language performance. Conclusion: Very early bilateral cochlear implantation may result in age-appropriate language skills already at the age of 2 years. Monolingualism seems to a better condition for early language development with CI than bilingualism. Especially for word production, the daily duration of CI use and exposure time in a speechcharacterised environment seem to be additional positive factors. Monitoring the data-logs should be one important focus of professionals during the postoperative rehabilitation process to detect potential benefits and risks. These findings should be integrated into rehabilitative therapy and parent counselling.
CRIS-Team WoS Importer:2021-07-30

Associations between illness perceptions, word recognition, and perceived sound quality in cochlear implant users - Lehmann, Effi; Glaubitz, Cynthia; Heinze-Köhler, Katharina; Liebscher, Tim; Hoppe, Ulrich (International Journal of Audiology, 2024)
Objective: Illness perceptions refer to thoughts and ideas an individual has about an illness. The aim was to understand how cochlear implant (CI) users’ illness perceptions, in addition to their monosyllabic word recognition abilities, are associated with their self-perceived sound quality. Design: Data were collected during routine CI check-up appointments. Participants completed the Brief Illness Perception Questionnaire (assessing their illness perceptions) and the Hearing Implant Sound Quality Index (assessing their subjective sound quality). Additionally, monosyllabic word recognition abilities were measured with the Freiburg Monosyllable Word Test. Hierarchical regression analysis were utilised to model users’ sound quality ratings. Participants’ age was entered first as a control variable. In the next step, monosyllabic word recognition was entered. Finally, participants’ illness perceptions were entered. Study sample: Fifty-five participants with unilateral CI provision. Results: Monosyllabic word recognition was significant in the second step. When illness perceptions and monosyllabic word recognition were both included in the third step, illness perceptions, but not monosyllabic word recognition, were significant. The model explained 22% of the variance of subjective sound quality. Conclusions: Monosyllabic word recognition abilities and illness perceptions of CI users are important for their self-reported sound quality, but illness perceptions appear to be potentially more relevant.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Brief IPQ; Cochlear implant; HISQUI; illness perceptions; Leventhal’s Self-Regulatory Model; monosyllabic word recognition; self-reported sound quality

Auditory group therapy in adult cochlear implant rehabilitation - Glaubitz, Cynthia; Lehmann, E. K.; Weber, L.; Kulke, A. -M.; Hoppe, Ulrich (HNO, 2019)
BACKGROUND: Auditory training is an established intervention in adult cochlear implant (CI) aural rehabilitation. In most cases, training is implemented in an individual therapy setting. Increasing patient numbers and the associated time-economic and cost-related demands as well as psychosocial and communicative aspects support the use of aural group interventions. OBJECTIVES: This study aimed 1) to describe concepts and contents of group interventions for adult CI users and 2) to present results of a questionnaire-based evaluation. METHODS: Group interventions have been offered at the CI Centre Erlangen CICERO for several years. In Auditory Training Groups, exercises have priority, while Thematic Group Workshops focus on psychosocial aspects and provide information for the participants. The Auditory Training Groups were evaluated based on a patient questionnaire. Additionally, the reliability of the questionnaire was analyzed. RESULTS: The median overall satisfaction of CI users participating in Auditory Training Groups was rated as good. Training of speech perception in noise as well as communicative exchange are of great importance for CI users. They rated the therapeutic design as very good to good. Reliability analysis showed significant positive intercorrelations of the questionnaire items. CONCLUSION: Group interventions are well accepted by CI users and represent a useful complement to individual therapy during the rehabilitation process. As group interventions place special demands on patients and therapists, structured and well-proven concepts should be used in practice.
EVALuna2:209999

Children with cochlear implant and additional disabilities benefit from consistent device use - Glaubitz, Cynthia; Liebscher, Tim; Hoppe, Ulrich (International Journal of Pediatric Otorhinolaryngology, 2022)
Objectives: Although the prevalence of additional disabilities (AD) in children with a cochlear implant (CI) is high, children with such disabilities are often excluded from clinical studies, or their specific characteristics are only partially included. The literature shows that several factors need to be considered in evaluating auditory and language development in CI children with AD, including demographic variables as well as the severity and type of disability. Current findings on device use in children show correlations with auditory and language outcome, but little is known about device use specifically in children with AD. The purpose of this study was to determine the auditory and language outcome of CI children with AD and to analyse their datalogging-based daily device use, both 1 year and 2 years after implantation. In addition, any potential correlations between outcome and device use were to be identified.Methods: A cohort of 32 CI children with 5 different types of AD were included in this retrospective analysis. The children's auditory and language outcome was assessed by the parental questionnaires LittlEARS and ELFRA and by the professional observation tool CAP (Categories of Auditory Performance) 1 and 2 years after implantation. Longitudinal device use was analysed by using the CI system-integrated data-logging; daily duration of CI use, number of coil disconnections and exposure to different listening scenes were recorded.Results: Overall, the cohort's auditory and language performance showed significant progress over time, while reduced abilities became more obvious after 2 years of CI experience. The mean daily duration of CI use increased significantly from 7.8 +/- 2.8 to 8.2 +/- 2.7 h after 2 years. High numbers of daily coil disconnections were detected, with a significant mean decrease from 83.4 +/- 73.1 to 66.3 +/- 54.6 whereas the percentage exposure to different listening environments was widely stable over time. Significant rank correlations were identified between outcomes measured by ELFRA and CAP with daily duration of CI use, numbers of coil disconnections and percentage of exposure to speech-characterised listening scenes.Conclusion: The auditory and language outcome in CI children with AD is variable, but it progresses over time. Children benefit from a consistent daily device use as well as from a high exposure to speech-characterised environments. Device use should be monitored constantly, with particular focus on daily duration of CI use and, in particular, on the number of coil disconnections if children have a severe motor impairment. Objective data-logging is an important addition to outcome assessment by testing, observations and parental questionnaires. Although assessment in children with AD is a major challenge for professionals, comprehensive assessment is needed to improve cochlear implant services with special adaption to children with AD, and this should include audiological, development-related and psychosocial information. A unified system to classify types of disabilities could help to improve procedures for analysing different outcomes.
CRIS-Team WoS Importer:2022-10-07

Correction to: Illness perceptions in cochlear implant users – a longitudinal study (European Archives of Oto-Rhino-Laryngology, (2024), 10.1007/s00405-024-08963-9) - Lehmann, Effi; Heinze-Köhler, Katharina; Glaubitz, Cynthia; Liebscher, Tim; Engler, Max; Hoppe, Ulrich (European Archives of Oto-Rhino-Laryngology, 2025)
The article “Illness perceptions in cochlear implant users – a longitudinal study”, written by Effi Katharina Lehmann, Katharina Heinze-Köhler, Cynthia Glaubitz, Tim Liebscher, Max Engler and Ulrich Hoppe, was originally published under exclusive license to The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024. As a result of the subsequent decision to publish the article under the open access model, the article’s copyright notice was changed on 6 December 2024 to © The Author(s) 2024 and the article is now distributed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0. Open access funding enabled and organized by Projekt DEAL. The original article has been corrected.
CRIS-Team Scopus Importer:2025-01-31

Frühe Sprachleistungen im Fragebogen ELFRA: Auswertung multizentrischer Daten von Kindern nach bilateraler Cochleaimplantatversorgung - Glaubitz, Cynthia; Beck, Rainer; Liebscher, Tim; Aschendorff, Antje; Kreibohm-Strauß, Kerstin; Kronesser, Dominique; Seebens, Yvonne; Streicher, Barbara; Kröger, Stefanie (HNO, 2024)
Background: Very early bilateral cochlear implant (CI) provision is today’s established standard for children. Therefore, the assessment of preverbal and verbal performance in very early stages of development is becoming increasingly important. Performance data from cohorts of children were evaluated and presented based on diagnostic assessment using chronological age (CA) and hearing age (HA). Methods: The present study, as part of a retrospective multicentre study, included 4 cohorts (N = 72–233) of children with bilateral CI without additional disabilities. Their results in the German parent questionnaires Elternfragebögen zur Früherkennung von Risikokindern(ELFRA‑1 and ELFRA-2) subdivided for CA and HA were statistically analysed. The data were also analysed in terms of mono-/bilingualism and age at CI provision. Results: Overall, verbal performance in relation to CA was lower than in relation to HA. Preverbal skills were largely CA appropriate. Children with bi-/multilingual language acquisition performed significantly lower. Verbal performance in ELFRA‑2 referenced to CA was negatively correlated with age at CI provision. Conclusion: In the case of early CI provision, CA should be the preferred reference mark in preverbal and verbal assessment in order to obtain exact individual performance levels and avoid bias in results. The percentiles determined are of limited use as generally valid reference values to which the individual performance of bilaterally implanted children could be compared. Further multicentre studies should be initiated.
CRIS-Team Scopus Importer:2024-06-21
Keywords: ACIR; Gestures; Hearing loss; Prelingual skills; Reference values

Hörtherapeutische Gruppenkonzepte in der Cochleaimplantat-Rehabilitation bei Erwachsenen - Glaubitz, Cynthia; Lehmann, E. K.; Weber, Lena; Kulke, A. ‑.M.; Hoppe, Ulrich (HNO, 2019)
Background: Auditory training is an established intervention in adult cochlear implant (CI) aural rehabilitation. In most cases, training is implemented in an individual therapy setting. Increasing patient numbers and the associated time-economic and cost-related demands as well as psychosocial and communicative aspects support the use of aural group interventions. Objectives: This study aimed 1) to describe concepts and contents of group interventions for adult CI users and 2) to present results of a questionnaire-based evaluation. Methods: Group interventions have been offered at the CI Centre Erlangen CICERO for several years. In Auditory Training Groups, exercises have priority, while Thematic Group Workshops focus on psychosocial aspects and provide information for the participants. The Auditory Training Groups were evaluated based on a patient questionnaire. Additionally, the reliability of the questionnaire was analyzed. Results: The median overall satisfaction of CI users participating in Auditory Training Groups was rated as good. Training of speech perception in noise as well as communicative exchange are of great importance for CI users. They rated the therapeutic design as very good to good. Reliability analysis showed significant positive intercorrelations of the questionnaire items. Conclusion: Group interventions are well accepted by CI users and represent a useful complement to individual therapy during the rehabilitation process. As group interventions place special demands on patients and therapists, structured and well-proven concepts should be used in practice.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Auditory training; Aural therapy; Cochlear implant; Group therapy; Questionnaire evaluation

Illness perceptions in cochlear implant users – a longitudinal study - Lehmann, Effi; Heinze-Köhler, Katharina; Glaubitz, Cynthia; Liebscher, Tim; Engler, Max; Hoppe, Ulrich (European Archives of Oto-Rhino-Laryngology, 2024)
Purpose: ‘Illness perceptions’ refers to the thoughts and ideas a person has about an illness. According to Leventhal’s Self-Regulatory Model (SRM), changing the threatening illness perceptions of cochlear implant (CI) recipients can be a further step in optimizing hearing outcomes with the CI. The aims of the present study were to assess users’ illness perceptions and to determine whether perceptions change during six months of CI rehabilitation. Methods: One hundred and thirty-eight participants completed the Brief Illness Perception Questionnaire (Brief IPQ), assessing their illness perceptions on nine scales. Data were collected at a German CI center at first CI fitting and six-month follow-up. After first fitting, participants underwent intensive rehabilitation including auditory training, medical, audiological and psychological treatments. Results: At both assessments, participants tended to view their hearing impairment as a severe threat. On the Brief IPQ, the ‘consequences’ assessment improved during CI rehabilitation, which can be explained by the CI-induced hearing improvement. However, ‘understanding’ and ‘identity’ assessments worsened. This could be because CI recipients only come to realize the full complexity of their hearing impairment during rehabilitation. The other scales and the total score remained unaffected. Conclusions: Current practice in CI rehabilitation seems to be insufficient to improve threatening illness perceptions (except for perceived consequences). This may be because standard information often fails to reach the patients. The development and empirical validation of an intervention program to address individual illness perceptions in CI recipients could be helpful in this context. Further research will be needed to confirm the results.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Brief IPQ; Cochlear implant (CI); Common-sense model of illness representations (CSM); Coping; Hearing impairment; Illness perceptions; Leventhal’s Self-Regulatory Model (SRM)

Impact of CI use and CI fitting on speech production in very early cochlear-implanted infants Bedeutung von CI-Nutzungsverhalten und CI-Anpassung für sprachproduktive Leistungen sehr früh cochleaimplantierter Kinder - Glaubitz, Cynthia; Liebscher, Tim; Hoppe, Ulrich (HNO, 2020)
Background: Children’s age at implantation is an important factor for their outcome in auditory and language skills with a cochlear implant (CI). CI use and frequency of CI fitting may also influence speech performance. Purpose of this study was to evaluate CI use and CI fitting of very early implanted infants and its potential influence on age-related speech production performance. Methods: Data of 34 bilaterally cochlea-implanted infants (age at CI in months: M = 8,8; SD = 1,7) were included. During the third year of life speech production performance was evaluated and related to datalogging-based CI use and number of CI fitting sessions. Results: About half of the cohort achieved speech production level within the normal range of hearing peers. Daily time of CI use was approximately 8 h. Analysis of listening environment showed that infants were exposed most of the time to quiet environment and least amount of time to speech in noise. Daily time of CI use seems to be a significant predictor of speech production, speech-exposition particularly predicts word production. Number of daily disconnection between CI-processor and implant as well as the monthly number of CI fitting sessions were not correlated with speech production. Conclusion: Very early cochlear implanted infants may achieve age-appropriate speech production performance in the third year of life. Time of daily CI use in the study cohort is comparable to results of other studies. Time of daily CI use and exposure to speech seem to be important factors for early speech production. These findings should be integrated in pre- and postoperative parent counselling.
CRIS-Team Scopus Importer:2020-09-25
Keywords: CI use; Cochlear implant; Data logging; Language development; Speech production

Sprachentwicklungstest für drei- bis fünfjährige Kinder (3;0–5;11 Jahre) – Diagnostik der Sprachentwicklung und der auditiven Gedächtnisleistungen: Retrospektive Auswertung der Ergebnisse bei Kindern mit bilateraler Cochleaimplantatversorgung im Kindesalter - Streicher, Barbara; Kreibohm-Strauß, Kerstin; Kröger, Stefanie; Kronesser, Dominique; Seebens, Yvonne; Glaubitz, Cynthia; Metzeld, Dennis; Lang-Roth, Ruth (HNO, 2025)
Background: Fitting of a cochlear implant (CI) influences the development of auditory memory and thus the development of speech. Speech development is a prerequisite for the acquisition of written language and reading and, thus, the later educational biography. Materials and methods: Language development tests for 3–5-year-old children (SETK 3–5) represent a standardized procedure to assess receptive and expressive speech development as well as auditory memory. In a retrospective cross-sectional study, data of children who were fitted with bilateral CIs from six CI centers of the ACIR (Arbeitsgemeinschaft CI Rehabilitation) were evaluated. The study group was divided into groups that were analyzed on the basis of age (chronological age; LA) and hearing experience with CI (hearing age; HA). In addition, a distinction was made between CI surgery before the age of 1 year (CI ≤ 12 months) and CI surgery from the second to the fourth year of life (CI > 12 ≤ 48 months). The study group was then subdivided according to the SETK 3;0–3;11 years test into G1LA (CI ≤ 12 months), G2LA (CI > 12 ≤ 48 months), G1HA (CI ≤ 12 months), and G2HA (CI > 12 ≤ 48 months). The study group for the SETK 4;0–5;11 years test was subdivided into G3LA (CI ≤ 12 months), G4LA (CI > 12 ≤ 48 months), G3HA (CI ≤ 12 months), and G4HA (CI > 12 ≤ 48 months). Results: The groups G1LA, G1HA, G3LA, and G3HA (CI ≤ 12 months) achieved age-appropriate values in all subtests of the SETK (3–5). Children who receive CI within the second year of life catch up in terms of language acquisition and some also develop language skills, but the T scores are below the age-adapted norm values. Children with a multilingual background show results below the norm of their hearing peers in both test settings (chronological age and hearing age). Conclusion: Early provision of CI in the first year of life is an important prerequisite for children to develop age-appropriate language skills. Nevertheless, there is wide variation within the groups, so that speech diagnostics and therapy are required as part of follow-up treatment during primary language acquisition to detect and avoid major language delay.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Language development; Language development disorders; Prostheses and implants; Rehabilitation; Rehabilitation outcome

Sprachentwicklungstest für zweijährige Kinder (2;0–2;11 Jahre) – Auswertung multizentrischer Daten von Kindern mit Cochleaimplantat nach bilateraler Versorgung - Kröger, Stefanie; Aschendorff, Antje; Glaubitz, Cynthia; Kreibohm-Strauß, Kerstin; Kronesser, Dominique; Seebens, Yvonne; Streicher, Barbara; Overlach, Fabian; Rother, Stephanie; Beck, Rainer (HNO, 2024)
Background: Age-appropriate speech development is a primary aim of the rehabilitation of children treated with cochlear implants (CI). Various assessment tools are available, including the speech development test for 2‑year-olds (SETK-2). All tests are normalized to normal-hearing children; additionally, results are evaluated according to age and the duration of CI (hearing age). The present study presents current practices and evaluates them as far as is possible. Materials and methods: In a multicentric retrospective study, 375 SETK‑2 datasets of congenitally deaf children treated with CI from five centers were included. All children had been treated before the fourth year of life, and the interval between treatment of the two sides was less than 12 months. Results: In the analyses according to age and hearing age, all subtests in the observed groups, with the exception of word comprehension, showed significantly worse results than the normative values. Isolated results demonstrated results similar to or even better than the normative values. The more complex the tested performance, the higher the proportion of conspicuous test results. The timepoint of implantation had no significant influence on test performance. Conclusion: The SETK‑2 should be evaluated according to chronological age; otherwise, the progress of early speech development may be incorrectly assessed and interventions initiated too late. Moreover, evaluation according to hearing age disregards the child′s cognitive skills.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Accompanying diagnostics; Cochlear implant; Congenital deafness; Rehabilitation; Speech development disorders

The LittlEARS® Auditory Questionnaire: An analysis of multicentre data of children after early bilateral cochlear implant placement Der LittlEARS® Hörfragebogen: Auswertung multizentrischer Daten von Kindern nach früher bilateraler Cochleaimplantatversorgung - Seebens, Yvonne; Metzeld, Dennis; Streicher, Barbara; Glaubitz, Cynthia; Kronesser, Dominique; Kreibohm-Strauß, Kerstin; Helbig, Silke; Schäfer, Karolin; Kröger, Stefanie; Beck, Rainer; Aschendorff, Antje (HNO, 2024)
Background: In order to optimise the support of children with cochlear implants (CI), it is very important to detect slow developmental processes as early as possible. Data from the LittlEARS® Auditory Questionnaire (LEAQ) from children with early bilateral CI are evaluated and presented in relation to age and hearing age and compared with language development data recorded later. Materials and methods: This retrospective multicentre study included data from a total of 554 children for whom at least one LEAQ was completed during the course of CI rehabilitation. Children without additional disabilities who received bilateral simultaneous or sequential CI treatment were included. Results: As expected, there are high correlations between hearing age (HA) and the overall LEAQ total score. When analysed according to chronological age (CA), development runs roughly parallel to the development of children with normal hearing, albeit at a lower level. Children implanted early up to an age of ≤ 12 months consistently achieve approximately 7–8 raw points more. Only the LEAQ results of the later test times (from the age of 18 months) correlate with some areas of the speech development test for children (SETK; areas 3–5). Conclusion: The earliest possible detection of critical developmental processes in children with CI is extremely important. In the case of very early CI fitting, the CA should be used as a reference measure in diagnostics. The LEAQ values determined for the group of children with CI are suitable to a limited extent as generally valid reference values for children with early bilateral CI. Further studies should continue to work out the correlations between early preverbal development and later speech development.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Chronological age; Hearing development; Hearing loss; Language development; Reference values

Word production in children with cochlear implant based on chronological age and hearing age Hör- und Lebensalter-bezogene Wortproduktion von Kindern mit Cochlea-Implantat - Glaubitz, Cynthia; Geiss, Katrin T.; Hoppe, Ulrich (Laryngo-Rhino-Otologie, 2022)
Background For congenitally deaf children, an early bilateral provision with cochlear implant (CI) is a favourable condition for language acquisition. The objective of the present study was to determine the word production in CI children. The focus was on a comparison of chronological age and hearing age performance and on the evaluation of potential effects of multilingualism, additional disabilities and age at provision. Methods The data of 62 children with bilateral CI (age at provision in months M= 12,1; SD = 6,2) were retrospectively analysed. Vocabulary was assessed by the test Aktiver Wortschatztest für 3- bis 5-jährige Kinder – Revision and compared for chronological age and hearing age. Group comparisons and correlation analysis was conducted regarding multilingualism, additional disabilities and age at provision. Results The cohort performed significantly better when referenced o hearing age: level were within or above the norm in more than 50 %; referenced to chronological age in around 37 %. The descriptive performance differences for multilingualism and additional disabilities were only significant for children with both characteristics. Performance of monolingual children without additional disabilities was not significantly associated with age at provision. Conclusion CI children may achieve an adequate expressive vocabulary at the age of 3 to 5 years. Multilingualism and additional disabilities seem to be particular challenges for CI children and need a more precise definition in further studies. The use of both chronological and hearing age as reference marks allows a differentiated assessment of the language status. This may lead to benefits in therapeutic interventions and parent councelling.
CRIS-Team Scopus Importer:2022-09-30
Keywords: AWST-R; Cochlea-Implantation; expressive Sprache; Höralter; Mehrsprachigkeit; Sprachdiagnostik; Sprachentwicklung; Sprachproduktion; Wortschatz; Zusatzbeeinträchtigung